2010
DOI: 10.1155/2010/290516
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Epigallocatechin Gallate Exhibits Anticancer Effect in Human Pancreatic Carcinoma Cells via the Inhibition of Both Focal Adhesion Kinase and Insulin-Like Growth Factor-I Receptor

Abstract: The exact molecular mechanism by which epigallocatechin gallate (EGCG) suppresses human pancreatic cancer cell proliferation is unclear. We show here that EGCG-treated pancreatic cancer cells AsPC-1 and BxPC-3 decrease cell adhesion ability on micro-pattern dots, accompanied by dephosphorylations of both focal adhesion kinase (FAK) and insulin-like growth factor-1 receptor (IGF-1R) whereas retained the activations of mitogen-activated protein kinase and mammalian target of rapamycin. The growth of AsPC-1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 30 publications
0
30
0
1
Order By: Relevance
“…EGCG has been also found to aid retained activation of MAPK signaling, suppressed growth, reduced cell viability, and increased apoptosis in these cells in a dose-dependent manner [158].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…EGCG has been also found to aid retained activation of MAPK signaling, suppressed growth, reduced cell viability, and increased apoptosis in these cells in a dose-dependent manner [158].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…The study further stated that EGCG inhibitsTNFα-induced activation of NF-κB and consequently secretion of pro-inflammatory and invasion-promoting proteins like IL-8 and uPA[157]. Moreover, previous studies have demonstrated that EGCG decreases cell adhesion ability on micro-pattern dots, accompanied by dephosphorylation of both focal adhesion kinase and insulin-like growth factor-1 receptor (IGF-1R) in AsPC-1 and BxPC-3 cells[158] [159] …”
mentioning
confidence: 98%
“…EGCG inhibits IL-6-induced VEGF expression and angiogenesis via suppressing Stat3 activity in gastric cancer [119]. ECCG abolishes the activation of FAK and suppresses more than 50% of cell proliferation without evidence of apoptosis analyzed by PARP cleavage [124]. EGCG inhibits cell proliferation and AKT phosphorylation at Ser473 in MDA-MB-231 and A549 cells [125].…”
Section: (−)-Epigallocatechin-3-gallatementioning
confidence: 99%
“…Este tercer proceso recibe el nombre de immune surveillance (vigilancia inmune) y es llevada a cabo principalmente por células NK y linfocitos T. Shimizy y col. 83 demostraron un efecto antienvejecimiento del té verde sobre el sistema inmune, contrarrestando la disminución de la immune surveillance causada por el envejecimiento y protegiendo el sistema inmune de cambios adversos ante la presencia de carcinógenos 84 . Adicionalmente, el té puede ejercer su efecto protector frente al cáncer de mama al reducir la expresión del factor de transcripción NFkB (Nuclear Factor kappa B) y su actividad transcripcional orquestada relacionada con procesos inflamatorios 85,86 .…”
Section: Autoresunclassified